Genetic parameters estimates in the maize population CPATC-3 in two locals of Sergipe State, Brazil - Carvalho, Hélio Wilson Lemos de; Leal, Maria de Lourdes da Silva; Santos, Manoel Xavier dos; Souza, Evanildes Menezes de (Pesquisa Agropecuaria Brasileira, 2003)
From 1999 to 2001, the maize population CPATC-3 was submitted to three selection cycles among and within half sib families in two sites of Sergipe State in order to obtain genetic parameters estimates and to verify the behavior of the genetic variability for ear weight. In each selection cycle, 196 half sib families were evaluated in a completely randomized block design with two replications per local and the recombination of the best families within the same agricultural year was made. The results showed highly significant differences among the families from the base population and for all selection cycles, evidencing the genetic variability presence for ear weight. The genetic parameters estimates showed that the maize population CPATC-3 presents genetic variability for increasing ear weight and offers good perspectives to continue the breeding program.